Fluorescent Silicon Nanorods-Based Nanotheranostic Agents for Multimodal Imaging-Guided Photothermal Therapy - Cui, Mingyue (Nanomicro Lett, 2019)
The utilization of diagnosis to guide/aid therapy procedures has shown great prospects in the era of personalized medicine along with the recognition of tumor heterogeneity and complexity. Herein, a kind of multifunctional silicon-based nanostructure, i.e., gold nanoparticles-decorated fluorescent silicon nanorods (Au@SiNRs), is fabricated and exploited for tumor-targeted multimodal imaging-guided photothermal therapy. In particular, the prepared Au@SiNRs feature high photothermal conversion efficiency (~ 43.9%) and strong photothermal stability (photothermal performance stays constant after five-cycle NIR laser irradiation), making them high-performance agents for simultaneously photoacoustic and infrared thermal imaging. The Au@SiNRs are readily modified with targeting peptide ligands, enabling an enhanced tumor accumulation with a high value of ~ 8.74% ID g(−1). Taking advantages of these unique merits, the Au@SiNRs are superbly suitable for specifically ablating tumors in vivo without appreciable toxicity under the guidance of multimodal imaging. Typically, all the mice treated with the Au@SiNRs remain alive, and no distinct tumor recurrence is observed during 60-day investigation. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40820-019-0306-9) contains supplementary material, which is available to authorized users.